Evaluation of immune response to hepatitis B vaccine among health care workers at a tertiary care hospital in south India: a retrospective record based study - Siddaiah, Archana; Chandralekha, Kona; Dore, Apoorva; Ramesh, Naveen; Joseph, Bobby (International Journal Of Community Medicine And Public Health, 2021)
Seroprevalence of hepatitis B virus (HBV) among healthcare workers (HCWs) is two to four times higher than that of the general population due to repeated exposure. To determine the hepatitis B (hep B) vaccination status, non-response rate to (hep B) and its determinants among HCWs at a tertiary care teaching hospital in south India. A secondary analysis of the medical records of a group of HCWs who joined the hospital from 1st January 2015 to 31st December 2016 was done. A total of 451 HCWs received the vaccine at the study hospital. Mean age of the HCWs was 25.3±6.1 years, majority 374 (82.1%) of them were females and joined as staff nurses 213 (47.2%). Only 164 (36.3%) had received all 3 doses of hep B vaccination. Complete vaccination with (hep B) among HCWs was poor. Health education and suitable administrative controls must be instituted to ensure protection.